Pathogenicity of Carbapenems and Third Generation Cephalosporins Resistant K. pneumoniae in Murine Urinary System - K. Rhumaid, Abdulkadir; Al-Mathkhury, Harith J.F. (Iraqi Journal of Science, 2023)
One hundred and nine clinical lactose fermenter isolates were collected from different samples (urine, stool, wound swab, blood, and sputum) , in a period from February 2014 till May 2014. All samples gathered from Alyarmok laboratories, Alkadimiya laboratories, and Baghdad teaching laboratories which are situated at Baghdad city. Fifty three (48,62%) isolates were identified as Klebsiella pneumoniae depending on microscopic characterization , conventional biochemical tests and then the identification confirmed with API 20E system . The rest of 56(51, 38%) isolates represented other bacteria.Susceptibility test was achieved to all fifty-three K. pneumoniae isolates using five antibiotic disks (Ceftazidime, Ceftriaxone, Cefotaxime, Imipenem, and Meropenem). Most of tested isolates were susceptible to Meropenem and Imipenem, 90.5% and 77.3%, respectively, and less susceptible to third generation Cephalosporin. Pathogenicity of Carbapenems and the third generation Cephalosporins resistant K. pneumoniae in murine urinary system in this study revealed Cabrapenem resistant isolates (K2 and K3) displayed severe histopathological changes compared to the third generation Cephalosporins resistant isolates (K6 and K46).